Revisiting the classification of Gallo-Italic: a dialectometric approach. (24th August 2017) - Tamburelli, Marco; Brasca, Lissander
Abstract: While Gallo-Italic varieties clearly belong to the Romance language family, their subgrouping as either Gallo-Romance or Italo-Romance has been the source of disagreement in the classificatory literature. While earlier analyses tended to classify Gallo-Italic as Gallo-Romance (notably Schmid, 1956 ; Bec, 1970–1971 ), later work has either argued for or tacitly assumed a classification of Gallo-Italic as part of the Italo-Romance branch, a view that is both different from as well as irreconcilable with the earlier Gallo-Romance classifications. In this article, we aim to contribute to the development of an empirically based classification of Gallo-Italic through the use of dialectometry applied to atlas corpora, and specifically through the measurement of Levenshtein distance. Using three wordlists (Swadesh 100, Swadesh 200, Leipzig–Jakarta) and comparing twenty-six linguistic varieties across Italy and south-eastern France, we show that Gallo-Italic is best classified as a third subgroup within the Gallo-Romance branch. Our results also clearly identify all the major bundles of isoglosses established through traditional dialectological methods and confirm Gallo-Italic as a relatively homogenous group distinct from Italo-Romance.